The earliest neuronal responses to hypoxia in the neocortical circuit are glutamate-dependent - Omer Revah; Efrat Lasser-Katz; Ilya A. Fleidervish; Michael J. Gutnick (Neurobiology of Disease, 2016)
Soon after exposure to hypoxia or ischemia, neurons in cortical tissues undergo massive anoxic depolarization (AD). This precipitous event is preceded by more subtle neuronal changes, including enhanced excitatory and inhibitory synaptic transmitter release. Here, we have used patch-in-slice techniques to identify the earliest effects of acute hypoxia on the synaptic and intrinsic properties of Layer 5 neurons, to determine their time course and to evaluate the role of glutamate receptors in their generation. Coronal slices of mouse somatosensory cortex were maintained at 36 °C in an interface chamber and challenged with episodes of hypoxia. In recordings with cell-attached electrodes, the open probability of Ca2+-dependent BK channels began to increase within seconds of hypoxia onset, indicating a sharp rise in [Ca2+]i just beneath the membrane. By using a high concentration of K+ in the pipette, we simultaneously monitored the membrane potential and showed that the [Ca2+]i rise was not associated with membrane depolarization. The earliest hypoxia-induced synaptic disturbance was a marked increase in the frequency of sPSCs, which also began soon after the removal of oxygen and long before AD. This synaptic effect was accompanied by depletion of the readily releasable transmitter pools, as demonstrated by a decreased response to hyperosmotic solutions. The early [Ca2+]i rise, the early increase in transmitter release and the subsequent AD itself were all prevented by bathing in a cocktail containing blockers of ionotropic glutamate receptors. We found no evidence for involvement of pannexin hemichannels or TRPM7 channels in the early responses to hypoxia in this experimental preparation. Our data indicate that the earliest cellular consequences of cortical hypoxia are triggered by activation of glutamate-gated channels.